Device and method for detecting air permeability of unconsolidated layer of continuous casting powder
By measuring the gas flow rate and pressure loss in the protective slag loose layer and determining the critical gas flow rate, the problem that existing detection methods are difficult to reflect the breathability and tumbling phenomenon of the protective slag loose layer is solved, and accurate detection and characterization of the breathability of the protective slag loose layer is achieved.
Patent Information
- Application Number
- CN202510098027.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing methods for breathability detection of porous dielectric material layers are difficult to accurately reflect the breathability and churning of the loose layer of the protective slag during continuous casting, which affects the use effect of the protective slag and the surface quality of the casting billet.
Using a detection device and method, the pressure loss of gas through the protective slag loose layer is measured through a gas flowmeter and a pressure detection system, and the air permeability of the loose layer is quantitatively characterized by critical gas flow parameters.
This method can effectively reflect the breathability and tumbling characteristics of the loose layer of protective slag in the continuous casting process, provide accurate detection results, guide the production and use of protective slag, and avoid affecting the anterior flow and the surface quality of the casting blank.
Smart Images

Figure CN119880736A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting technology, and relates to a device and method for detecting the air permeability of a loose layer of continuous casting protection slag. Technical Background
[0002] In the field of steel production, continuous casting, as the main forming process of molten steel, has an important impact on steel production and quality. In order to ensure the smooth continuous casting process and improve the surface quality of the ingot, mold casting is used in production. After the mold slag is added to the upper mouth of the crystallizer, it gradually heats up and melts, forming a multilayer structure of loose layer, sintered layer and slag layer in the vertical direction, which has the functions of absorbing molten steel inclusions, preventing secondary oxidation of molten steel and heat insulation. The permeability of the loose layer has an important influence on its thermal insulation effect, the formation of layered structure and the use effect. On the one hand, the heat transfer mode in the loose layer is mainly gas convection heat transfer, and its permeability will affect the gas flow, change the internal heat transfer and the melting process of the mold slag, and then affect its thermal insulation performance; on the other hand, during the heating process of the mold slag, chemical reactions such as carbonate decomposition and carbonaceous material combustion will release gas. During the upward movement of the gas, if the loose layer is not permeable enough, these gases will cause the surface of the loose layer to churn, destroy the structural stability of the slag layer, and thus affect the overall use effect of the mold slag. In actual continuous casting on-site production, the size of loose particles is an important factor affecting permeability. Generally, the smaller the loose layer particles, the weaker the permeability and the better the thermal insulation performance. For example, in the high-speed continuous casting process of thin slabs, the loose layer of protective slag in the crystallizer is required to have weak permeability, small convective heat transfer, and good thermal insulation. It is necessary to match the casting with protective slag with smaller particle size; for conventional slab stainless steel continuous casting, it is necessary to match protective slag with larger particles and stronger permeability to prevent the occurrence of churning of the loose layer of protective slag in the crystallizer. In summary, the permeability of the loose layer of protective slag is an important indicator of its product, which significantly affects the use effect of the protective slag in the casting process, so the effective and accurate characterization of this indicator is particularly critical.
[0003] In the field of continuous casting protective slag, there is a patent (application number 202010693943.2) that reflects the sintering performance of protective slag through the air permeability characteristics after heating. However, this method is mainly aimed at the sintered layer in the multi-layer structure of protective slag, not the loose layer, and it cannot characterize the thermal insulation effect and tumbling phenomenon of the loose layer. In addition, the loose layer of protective slag is composed of a large number of hollow particles of 100 to 1000 μm, which belongs to the field of porous media. For the detection of the air permeability of porous media, there have been studies and devices applied to the fields of sintered ore, concrete, blast furnace iron ore, porous ceramics, soil and rock. For example: the air permeability detection device and method of the loose layer of sintered ore with application numbers 201810301979.4 and 201711115735.9, by exhausting the upper part of the loose layer of sintered ore, the air permeability of the loose layer is reflected according to the gas pressure difference and flow rate. However, in the loose layer of protective slag, gas is formed at the bottom of the loose layer and moves upward. Therefore, the above method is difficult to truly reflect the impact of gas on the loose layer of protective slag during continuous casting, and it is also impossible to characterize the tumbling phenomenon of the loose layer. The detection method with application number 200910223393.1 reflects the permeability of the loose layer by the flame illumination intensity after the sintering ore is ignited. During the heating process of the protective slag, flames will also be generated due to the combustion of carbonaceous materials. However, the carbonaceous material content of different types of protective slags varies significantly, so the flame intensity is significantly affected by the type of protective slag. Therefore, this method is also not suitable for the detection of the permeability of the loose layer of protective slag. Application number 202410169235.7 analyzes the permeability of concrete based on spectral reflectance, but does not involve gas flow and cannot reflect the dynamic behavior of gas in the loose layer. In the study of blast furnace permeability, the permeability index was calculated based on pressure difference, gas flow rate or softening temperature, but the tumbling of the loose layer was not evaluated. In the research of porous ceramics, rocks and soils, the permeability is measured based on Darcy's law. Although the theory is mature, it fails to adapt to the characteristics of the loose layer of protective slag and the continuous casting process conditions, and cannot reflect the thermal insulation and tumbling phenomenon of the loose layer of protective slag in the crystallizer.
[0004] In summary, in the field of continuous casting, there is a lack of a device and method to reflect the permeability of the loose layer of protective slag in the crystallizer, and the existing porous medium material layer permeability detection method is difficult to meet the detection needs of the loose layer of protective slag. An accurate and effective method is urgently needed to detect the permeability of the loose layer of protective slag. Summary of the invention
[0005] In view of the fact that the existing method for detecting the air permeability of porous medium material layers is not suitable for crystallizer protective slag, the purpose of the present invention is to provide a device and method for detecting the air permeability of the loose layer of protective slag, which quantitatively characterizes the permeability of the loose layer through critical gas flow rate to reflect the thermal insulation and tumbling phenomenon of the loose layer of protective slag in the crystallizer during the continuous casting process.
[0006] In order to solve the above-mentioned technical problems, the present invention proposes a device and method for detecting the permeability of a loose layer of protective slag, wherein the device comprises: a gas cylinder for providing gas; a gas flow meter connected to the gas cylinder for controlling the gas flow; a transparent material tank for storing protective slag particle samples; a three-way valve connecting the gas flow meter and the material tank for adjusting the gas flow direction; a pressure detection system for measuring the pressure difference between the upper and lower loose layers of slag; and an air pipe connecting the gas cylinder, the three-way valve, the material tank and the pressure detection system to conduct the airflow.
[0007] The method comprises the following steps:
[0008] (1) adding a mold slag particle sample into the material tank to form a loose layer with a thickness of 30 to 100 mm;
[0009] (2) Provide gas through a gas cylinder and use a gas flow meter to adjust the flow so that the gas enters the loose layer of protective slag from the bottom of the tank;
[0010] (3) Gradually increase the gas flow rate and use the pressure detection system to measure the pressure loss of the gas through the loose layer;
[0011] (4) Record and draw the relationship curve between gas flow rate and pressure loss: when the loose layer is in a fixed state, the pressure loss increases with the increase of gas flow rate;
[0012] (5) Further increase the gas flow rate to cause the loose layer surface to churn and form a fluidized state, at which point the change in pressure loss tends to be stable;
[0013] (6) The corresponding gas flow rate is determined by the intersection of the fixed state and fluidized state pressure loss curves as the critical gas flow rate of the mold slag loose layer. The critical gas flow rate represents the strength of the permeability of the mold slag loose layer.
[0014] Preferably, the gas enters the loose layer of protective slag from the bottom of the tank through a three-way valve.
[0015] Preferably, the top of the material tank is provided with an opening connected to the atmosphere.
[0016] Preferably, the pressure detection system cooperates with a gas flow meter to implement a method for detecting the air permeability of a loose layer of protective slag.
[0017] Preferably, during the transition process of the loose layer of protective slag from a fixed state to a fluidized state, the gas flow rate corresponding to the intersection of the pressure loss curves of the two states is the critical gas flow rate.
[0018] Preferably, the smaller the critical gas flow rate is, the weaker the air permeability of the loose layer is, which means that the thermal insulation of the protective slag in the crystallizer is better during the continuous casting process.
[0019] Preferably, the larger the critical gas flow rate, the stronger the air permeability of the loose layer, which means that the protective slag in the crystallizer is less likely to churn during the continuous casting process.
[0020] Compared with the existing detection methods, the detection device and method of the air permeability of the loose layer of continuous casting mold slag of the present invention have the following beneficial effects:
[0021] In the present invention, the gas enters the mold slag loose layer from the bottom and moves upward. During the continuous casting process, the gas is formed at the bottom of the mold slag loose layer and moves upward. Therefore, the movement mode of the gas in the detection method is the same as that in the continuous casting process, which can effectively reflect the permeability and tumbling characteristics of the mold slag loose layer in the continuous casting process.
[0022] By adopting the device and method for detecting the permeability of the loose layer of protective slag provided by the present invention, a critical gas flow rate parameter is proposed to quantitatively characterize the permeability of the loose layer of protective slag through the relationship between gas flow rate and pressure loss, thereby providing guidance for the production of protective slag plants and the use of protective slag in steel mills, avoiding the impact of changes in the permeability of the loose layer on the smooth progress of continuous casting production and the surface quality of the ingot, and having great economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments are briefly introduced below. The drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained according to the structures shown in these drawings without creative work.
[0024] Figure 1 It is a schematic structural diagram of a device for detecting the air permeability of a loose layer of protective slag in an embodiment of the present invention;
[0025] Figure 2 The reproducibility of the test results of the air permeability of the loose layer of conventional slab protection slag in the embodiment of the present invention;
[0026] Figure 3 The test results of the air permeability of the loose layer of the thin slab continuous casting mold slag with different particle size compositions in the embodiment of the present invention;
[0027] Figure 4 The test results of the air permeability of the loose layer of conventional slab stainless steel protection slag with different particle sizes in the embodiment of the present invention are shown;
[0028] Figure 5 It is a flow chart of a method for testing the air permeability of a loose layer of protective slag in an embodiment of the present invention;
[0029] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described below in conjunction with the accompanying drawings in the embodiments of the present invention. It should be understood that the embodiments described herein are only part of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The main purpose of the present invention is to provide a device and method for detecting the air permeability of a loose layer of continuous casting mold slag, so as to solve the problem that the existing method for detecting the air permeability of a loose layer of porous media is difficult to effectively and accurately reflect the air permeability of the loose layer of the mold slag.
[0032] Please refer to Figure 1 The device and method for detecting the air permeability of the loose layer of continuous casting mold slag provided by the embodiment of the present invention include a gas cylinder 1, on which a gas flowmeter 2 is installed, and the gas cylinder 1, a material tank 3 and a pressure detection system 5 are connected through a three-way valve 4 and a gas pipe 6. After the gas comes out of the gas cylinder 1, it enters the loose layer from the bottom of the material tank 3. When the gas passes through the loose layer of the mold slag, it encounters resistance. Part of the gas flows from the three-way valve 4 to the pressure detection system 5 and records the relationship between the formed pressure loss and the gas flow rate.
[0033] Using the above-mentioned detection device and method for the air permeability of the loose layer of protective slag provided by the present invention, taking the measurement of the air permeability of the loose layer of conventional slab protective slag as an example, the specific operation steps are as follows:
[0034] S1. Place the protective slag particle sample in the material tank 3, and the loose layer thickness is 50 mm;
[0035] S2, open the gas cylinder 1, and use the gas flow meter 2 to adjust the flow rate to 0.5L / min;
[0036] S3. When the gas flow rate is stable, the pressure detection system 5 detects the pressure loss and records the gas flow rate;
[0037] S4, gradually increase the gas flow rate by 1L / min, 1.5L / min, 2L / min, 2.5L / min... until the surface of the loose layer of protective slag is churning;
[0038] S5. Draw the relationship curve between gas flow rate and pressure loss: when the loose layer is not churning, the pressure loss increases with the increase of gas flow rate, showing a fixed state;
[0039] S6. When gas passes through a fixed loose layer, the pressure loss follows the Eugen equation:
[0040]
[0041] in:
[0042] △P is the pressure loss through the loose layer, the unit is Pa.
[0043] L is the thickness of the loose layer, in meters.
[0044] dp is the equivalent spherical diameter of the protective slag particles, in m.
[0045] ρ is the gas density, kg / m3.
[0046] μ is the dynamic viscosity of the gas, with the unit being Pa·s.
[0047] v is the volume flow rate of the gas (the superficial velocity of the bed) in m / s.
[0048] ε is the porosity of the loose layer of particles (the ratio of the volume of interparticle gaps to the total volume, unitless).
[0049] S6. Further increase the gas flow rate to make the loose layer surface churn and form a fluidized state. At this time, the change of pressure loss tends to be stable.
[0050] S7. Determine the corresponding gas flow rate as the critical gas flow rate of the protective slag loose layer through the intersection of the fixed state and fluidized state pressure loss curves.
[0051] S8. The smaller the critical gas flow rate, the weaker the air permeability of the loose layer, and vice versa.
[0052] Embodiment 1
[0053] The permeability of the loose layer of conventional slab protection slag was tested three times according to steps S1 to S7. The results are as follows: Figure 2 It can be found that the critical gas flow rate of the three test results is 2.5L / min, which shows that the test results of the loose layer of continuous casting mold slag of the present invention have good reproducibility.
[0054] Embodiment 2
[0055] According to steps S1 to S8, the air permeability of the loose layer of the thin slab continuous casting mold slag with four different particle size compositions was tested. The particle size composition of the samples is shown in Table 1. From No. 1 to No. 4, the proportion of fine particles of 0.1 to 0.2 mm gradually increases. The air permeability test results of the samples are shown in Table 1. Figure 3The critical gas flow rate is shown in Table 1. The results show that with the increase of the proportion of 0.1-0.2mm fine particles in the slag, the critical gas flow rate of the loose layer tumbling decreases from 4.0L / min to 2.5L / min, indicating that the permeability of the loose layer gradually weakens. When the proportion of 0.1-0.2mm particles reaches 20wt%, the fixed-state pressure loss curve changes significantly, indicating that the permeability of the loose layer is significantly reduced, and the thermal insulation performance is correspondingly increased. The factory uses a protective slag particle size composition with a proportion of about 20wt% of 0.1-0.2mm particles, and has achieved good casting results.
[0056] Table 1 Effect of particle size composition of mold slag on permeability of thin slab
[0057]
[0058] Embodiment 3
[0059] This example tests the air permeability of the loose layer of conventional slab stainless steel protection slag with different particle size compositions, and the particle size composition is shown in Table 2. Using the method described in Example 1, the air permeability of the loose layer is tested and analyzed according to steps S1 to S8. The test results are shown in Figure 3 As shown, it can be seen that with the increase in the proportion of 0.1-0.2 mm particles in the protective slag, the critical gas flow rate of the loose layer tumbling decreases from 5.0 L / min to 4.0 L / min, indicating that the permeability of the loose layer gradually weakens. When the proportion of 0.1-0.2 mm particles is less than 10wt%, the fixed-state pressure loss curve changes significantly, and the permeability of the loose layer is significantly enhanced. The factory uses a protective slag particle size composition in which 0.1-0.2 mm particles account for no more than 10wt%, which effectively solves the tumbling phenomenon of the protective slag in the crystallizer during the casting process.
[0060] Table 2 Effect of particle size composition of stainless steel protection slag on permeability
[0061]
[0062] The above are only embodiments of the present invention, which are only used to explain the present invention rather than to limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A device for detecting the air permeability of a loose layer of continuous casting mold slag, comprising: Gas cylinders, used to provide gas; A gas flow meter, connected to the gas cylinder, is used to control the gas flow; Transparent material tank, used to store protective slag particle samples; The three-way valve connects the gas flow meter and the material tank to adjust the gas flow direction; the pressure detection system is used to measure the pressure difference between the upper and lower loose layers of slag; the gas pipe connects the gas cylinder, the three-way valve, the material tank and the pressure detection system to conduct the gas flow.
2. A method for testing the air permeability of a loose layer of continuous casting mold slag, comprising the following steps: (1) adding a mold slag particle sample into the material tank to form a loose layer with a thickness of 30 to 100 mm; (2) Provide gas through a gas cylinder and use a gas flow meter to adjust the flow so that the gas enters the loose layer of protective slag from the bottom of the tank; (3) Gradually increase the gas flow rate and use the pressure detection system to measure the pressure loss of the gas through the loose layer; (4) Record and draw the relationship curve between gas flow rate and pressure loss: when the loose layer is in a fixed state, the pressure loss increases with the increase of gas flow rate; (5) Further increase the gas flow rate to cause the loose layer surface to churn and form a fluidized state, at which point the change in pressure loss tends to be stable; (6) The corresponding gas flow rate is determined by the intersection of the fixed state and fluidized state pressure loss curves as the critical gas flow rate of the mold slag loose layer. The critical gas flow rate represents the strength of the permeability of the mold slag loose layer.
3. The device for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 1, characterized in that: The gas enters the loose layer of protective slag from the bottom of the tank through a three-way valve.
4. The device for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 1, characterized in that: The top of the material tank is provided with an opening which is connected to the atmosphere.
5. The device for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 1, characterized in that: The pressure detection system cooperates with the gas flow meter to implement the testing steps of the method described in claim 2.
6. The method for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 2, characterized in that: During the transition process of the loose layer of protective slag from a fixed state to a fluidized state, the gas flow rate corresponding to the intersection of the pressure loss curves of the two states is the critical gas flow rate.
7. The method for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 2, characterized in that: The smaller the critical gas flow rate, the weaker the permeability of the loose layer, which means that the thermal insulation of the protective slag in the crystallizer during the continuous casting process is better.
8. The method for detecting the air permeability of the loose layer of continuous casting mold slag according to claim 2, characterized in that: The larger the critical gas flow rate, the stronger the permeability of the loose layer, which means that the protective slag in the crystallizer is not likely to churn during the continuous casting process.
Citation Information
Patent Citations
Method for detecting air permeability of sintering mixture and sintering device
CN102062719A
Online detecting device and method of breathability of material layer of sintering cup
CN107894385A
An online detection system and control method for the air permeability of sintered mixtures
CN108507355B
Method and device for testing heating sintering characteristics of solid-state continuous casting covering slag
CN111812143A
A method and system for intelligent detection of concrete air permeability
CN117710380B